2016
DOI: 10.1177/1753465816667659
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profile of benralizumab in the management of severe eosinophilic asthma

Abstract: Despite several therapeutic choices, 10–20% of patients with severe uncontrolled asthma do not respond to maximal best standard treatments, leading to a healthcare expenditure of up to 80% of overall costs for asthma. Today, there are new important therapeutic strategies, both pharmacological and interventional, that can result in improvement of severe asthma management, such as omalizumab, bronchial thermoplasty and other biological drugs, for example, mepolizumab, reslizumab and benralizumab. The availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 81 publications
(107 reference statements)
0
28
0
Order By: Relevance
“…Outside of the mepolizumab clinical trial program, recent studies have shown that benralizumab can deplete blood eosinophils to a higher degree than mepolizumab or reslizumab, 50,51 and this differentiated mechanism of action has led some investigators to suggest that benralizumab might prove to be more efficacious than mepolizumab or reslizumab. 52 Although no head-to-head data exist, in the phase 3 SIROCCO (NCT01928771) and CALIMA (NCT01914757) trials, benralizumab reduced the annual rate of exacerbations by 28% to 51% versus placebo in patients with blood eosinophil counts of 300 cells/mL or greater at baseline, 14,15 which does not exceed the exacerbation reductions achieved in similar studies of mepolizumab and reslizumab. 17,18,20 Similarly, in a post hoc analysis of SIROCCO and CALIMA trials, benralizumab reduced the annual rate of exacerbations by 36% to 42% in patients with blood eosinophil counts of 150 cells/mL or greater at baseline by using an 8-week dosing regimen.…”
Section: Pharmacodynamic Biomarkers For Mepolizumab Treatment Responsementioning
confidence: 98%
“…Outside of the mepolizumab clinical trial program, recent studies have shown that benralizumab can deplete blood eosinophils to a higher degree than mepolizumab or reslizumab, 50,51 and this differentiated mechanism of action has led some investigators to suggest that benralizumab might prove to be more efficacious than mepolizumab or reslizumab. 52 Although no head-to-head data exist, in the phase 3 SIROCCO (NCT01928771) and CALIMA (NCT01914757) trials, benralizumab reduced the annual rate of exacerbations by 28% to 51% versus placebo in patients with blood eosinophil counts of 300 cells/mL or greater at baseline, 14,15 which does not exceed the exacerbation reductions achieved in similar studies of mepolizumab and reslizumab. 17,18,20 Similarly, in a post hoc analysis of SIROCCO and CALIMA trials, benralizumab reduced the annual rate of exacerbations by 36% to 42% in patients with blood eosinophil counts of 150 cells/mL or greater at baseline by using an 8-week dosing regimen.…”
Section: Pharmacodynamic Biomarkers For Mepolizumab Treatment Responsementioning
confidence: 98%
“…The absence of fucose sugar residue in the molecular structure of benralizumab results in a much higher affinity for the FcγRIIIa receptor, overcoming the inhibitory effects of serum blocking IgGs. 47 These features resulted in excellent efficacy data in terms of reduction of exacerbation rate and improvement in FEV1, 51 , 52 significant reduction (75%) of the OCS 53 average dose and a clear response after the first dose. 54 …”
Section: Eosinophils and Il-5mentioning
confidence: 95%
“…The benralizumab constant region (Fc) is afucosylated, leading to greater affinity for the Fc-gamma III receptor (FcγRIIIa) on the surface of the mast cells, basophils and natural killer cells, through which it induces ADCC on eosinophils and basophils. 47 This involves a nearly complete depletion of eosinophils in sputum and tissues (90% and 96%, respectively) and a total disappearance in the bone marrow and blood. 48 In Phase I and II RCTs on patients with severe eosinophilic asthma and peripheral eosinophils >300 cells/μL, SC benralizumab showed promising results, especially in terms of reducing EDN and ECP inflammation and inflammatory mediators as well as causing a significant reduction in blood eosinophils.…”
Section: Eosinophils and Il-5mentioning
confidence: 99%
“…Benralizumab is a fully humanized IgG1k afucosylated mAb which binds to the α-chain of the IL-5 receptor (IL-5R), with consequent inhibition of receptor activation mediated by IL-5 (Figure 1). 35 Afucosylation improves the interaction of benralizumab with its binding site and strongly induces the main feature of this drug, cell-mediated antibody-dependent cytotoxicity (ADCC) by natural killer (NK)-cells. Through ADCC, benralizumab can markedly reduce eosinophils and other IL-5R + cells, such as progenitors of eosinophils, basophils and ILC2s.…”
Section: Methodsmentioning
confidence: 99%